Fulfilling the Rights of Children in Vulnerable Areas of Violence through Women's Institutional Education with an Andragogic Approach - Purnamasari, Iin; Widodo, Suwarno; Maryanto, Sugeng; Cholifah, Nur (KnE Social Sciences, 2024)
This paper presents part of women’s empowerment as a form of community education carried out in area-based service programs. The urgency of this program is to realize child-friendly village management by optimizing women’s institutional strengthening. The potential and strategic location of an area has triggered problems such as women factory workers who are unable to carry out the role of the main and first educators for their children, the emergence of locations for prostitution practices, the emergence of the phenomenon of children being cared for by others (outside the nuclear family), and children with unclear legal status, children do not have population administration because they were born out of wedlock from immigrants who work in entertainment places (Karaoke Guides). The method applied is an andragogy approach to adult learning, in the form of training and mentoring, with 30% theoretical and 70% practice. The results obtained were in the form of strengthening the role of women’s institutions in managing child-worthy villages in the fields of education, health, and economy; increased legal protection of children; awareness of family law; clean and healthy lifestyle that cultivates; increased family economic literacy; decreased child violence and stunting rates. Through this program, women’s institutions at the village level can understand and carry out their role in managing child-worthy villages with indicators of the fulfillment of children’s rights and protection from various aspects. Keywords: education, andragogy, women’s institutions, rights, protection, children